If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(w + 3) = 8 Reorder the terms: 2(3 + w) = 8 (3 * 2 + w * 2) = 8 (6 + 2w) = 8 Solving 6 + 2w = 8 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2w = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 2w = 8 + -6 2w = 8 + -6 Combine like terms: 8 + -6 = 2 2w = 2 Divide each side by '2'. w = 1 Simplifying w = 1
| (3y-1)+(4y+7)= | | -80-10x=140 | | ln(2x+1)=3.25 | | 4u-26=-2(u+7) | | -10x-35+24x=6x+13 | | x+x+75+x-15=180 | | X+13x+42= | | 2lnx=ln(x+2) | | 205/x=5.54 | | 5(3x+2)-2=4(4x-3) | | (4/x^2) | | 23x+2y=-19 | | -3(-2x-2)=12 | | 2.6=3a | | 7b-10+69-3=83 | | y-42=180 | | 8(1+5)+5=12+5x | | 1-4lnx=lnx-9 | | 10f+8=11f+7 | | 6(y+1)=2y+18 | | 4m+10=36 | | 23+5x=111-3x | | 7(51)=10 | | -2(3-7)-4= | | x=11+7y | | 2b+b=7 | | 13+3x=3n-29 | | 3y-2=4(2y-3) | | 13+3x=-29-3n | | 2.6=0.2-4 | | -2a+(5a-3)-(3a+4)= | | 8-3k+6k=2k-3 |